KEDUDUKAN BADAN USAHA MILIK DESA (BUMDES) BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA: THE POSITION OF VILLAGE OWNED BUSINESS ENTITIES (BUMDES) BASED ON LAW NO. 11 OF 2020 CONCERNING JOB CREATION - HADI, JUSMAN KHAIRUL (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2021)
Law No. 6 of 2014 on Villages (Village Law) appears to construct Village-Owned Enterprise or Badan Usaha Milik Desa (BUM Desa) as a new form of business entity within the Indonesian legal sphere. BUM Desa is considered to be different from other variants of business entities in Indonesia. There are multiple interpretations regarding the status of BUM Desa, debating whether they are legal entities or not. This normative legal research discusses the legal aspects of BUM Desa following the promulgation of the Village Law. It concludes that: (1) theoretically BUM Desa meets the criteria as a public legal entity. The issuance of Law No.11 of 2020 on Job Creation confirms the status of BUM Desa as a legal entity; (2) BUM Desa is a public business entity with a unique character to villages different from other forms of business entity with private ownership such as limited companies and cooperatives. However, legal provisions on BUM Desa still contain logical inconsistencies regarding the basic conception of BUM Desa and Law 12/2011 does not yet include Perdes as statutory regulation. The confirmation of the status of BUM Desa legal entities needs to be complemented by synchronization with Law 12/2011 to strengthen the position of Perdes as the legal basis for the establishment of BUM Desa along with various other sectoral regulations